Management of Integrated Career Service: Upaya Peningkatan Daya Serap Lulusan Madrasah Aliyah Negeri 2 Brebes di Jenjang Perguruan Tinggi Negeri - Firdiasih, Tol'ah Aeni; Masruji, Masruji (Arfannur, 2023)
The meaning of education is to develop the potential of learners so that they are capable of facing real-life situations in accordance with the changing times. Therefore, an effective and efficient career management is needed in the process. The purpose of this research is to explain career guidance and counseling management, which includes planning, organizing, implementing, and supervising aspects, at MAN 2 Berbes. The research method used is qualitative with a phenomenological approach, aiming to describe in detail the phenomenon of the management of integrated career service: efforts to improve the absorption of graduates from Madrasah Aliyah Negeri 2 Brebes into state universities. Data collection techniques in this research include interviews, observations, and documentation. The research results show that the planning in the program of management of integrated career service at MAN 2 Brebes is in accordance with the established procedures. The organization of career guidance and counseling has also been executed well through departmentalizing job descriptions in each department based on competence and authority. The implementation of career guidance and counseling at MAN 2 Brebes, in general, has been running smoothly, covering individual, group, classical, and special services. Supervision is also well-managed using the CIPP approach (context, input, process, and product). The impact of career guidance has led to an increase in the absorption rate of MAN 2 Brebes graduates in state universities through academic achievement or report-based admissions. In 2021, the percentage of graduates accepted into state universities through academic achievement or report-based admissions was 23.15%. This increased by 19.38% in 2022 to reach 42.53%. In 2023, it further increased to 56.61%. In other words, there was an increase of 14.08% from 2022. ABSTRAK Makna Pendidikan adalah mengembangkan potensi perserta didin mampu menghadapi kehidupan sesungguhnya sesuai dengan perkembangan zaman. Maka dari itu dalam prosesnya dibutuhkan manajemen kariryang efektif dan efisien. Tujuan penelitian ini adalah menjelaskan manajemen bimbingan dan koseling karier mencakup aspek perencanaan, pengorganisasian, pelaksanaan, dan pengawasan di MAN 2 Berbes. Jenis penelitian yang digunakan yaitu kualitatif, dengan pendekatan fenomenologi, karena bermaksud menggambarkan secara rinci mengenai fenomena management of integrated career service: upaya peningkatan daya serap lulusan Madrasah Aliyah Negeri 2 Brebes di jenjang perguruan tinggi negeri. Teknik pengumpulan data dalam penelitian ini menggunakan wawancara, observasi, dan dokumentasi. Hasil penelitian menujukkan bahawa perencanaan dalam program management of integrated career service di MAN 2 Brebes sudah sesuai prosesdur. Pengorganisasian bimbingan dan konseling karier juga sudah dilaksanakan dengan baik melalui langkah departementasi job description pada masing-masing bagian sesuai dengan kompetensi dan kewenangannya. Pelaksanaan bimbingan dan konseling karier di MAN 2 Brebes secara umum sudah berjalan dengan baik, yakni layanan individu, kelompok, klasikal, dan khusus. Dan pengawasan juga sudah berjalan baik menggunakan pendekatan CIPP (context, input, process, dan product). Dampak dari bimbingan karir maka terjadi peningkatan daya serap lulusan MAN 2 Brebes yang diterima di jenjang perguruan tinggi negeri melalui jalur prestasi atau raport. Pada tahun 2021 yang diterima di perguruan tinggi negeri melalui jalur pretasi raport sebanyak 23,15%. Jumlahnya meningkat 19,38 % pada tahun 2022 menjadi 42,53%. Dan di tahun 2023 jumlahnya semakin meningkat menjadi 56,61 %. Dengan kata lain terjadi peningkatan sebanyak 14,08% dari tahun 2022. Kata Kunci: Management of Integrated Career Service, Daya Serap Lulusan,MAN 2 Brebes